Multiyear Population Dynamics of Ditylenchus dipsaci Associated with Phlox subulata - Schnabelrauch, L S (Journal of nematology, 1980)
Field population densities of Ditylenchus dipsaci associated with shoot tissue of Phlox subulata were monitored during two consecutive growing seasons and intervening periods of overwintering and plant storage. The population density increased significantly through four peaks during the first growing season, and decreased significantly during storage at 5-7 C or overwintering in the field. During the second growing season, there was only a single increase to a moderate population density, followed by a severe population decline associated with the poor physiological condition of the host. A simple model is proposed to explain the population dynamics of D. dipsaci during the first growing season